Ecological monitoring of social-hygienic conditions of the life and biological features of children with the different level of health - R. O. Osmanov; Z. G. Musayeva; S. O. Kurbiyeva (Юг России: экология, развитие)
The article is devoted to the analysis of sociological questioning data of mothers in Makhachkala for revealing the sociallyhygienic conditions and way of life of children, revealing groups with a different level of health. According to interrogation it is established, that 26,4 % have some vital restrictions connected with deviations of health. It is noted, that sick children have insufficient weight almost in 3 times more often, in 9 times lag physical activity than healthy children.